2007
DOI: 10.1007/s11882-007-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 receptor isoforms: Breaking through the complexity

Abstract: Interleukin (IL)-13 is an immunoregulatory cytokine secreted predominantly by activated T-helper type 2 (Th2) cells, and it has been identified as crucial in developing allergic inflammatory responses. Its diverse functions are mediated by a complex receptor system including IL-4 receptor alpha (IL-4Ralpha; CD124) and two other cognate cell surface proteins, IL-13Ralpha1 (CD213a1) and IL-13Ralpha2 (CD213a2). IL-13Ralpha1 forms a heterodimer with IL-4Ralpha that is a signaling IL-13 receptor. In contrast, IL-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 54 publications
(66 reference statements)
4
63
0
Order By: Relevance
“…This result is consistent with a previous gene-expression study in which the IL4Rα and IL13Rα1 chains were reported to be upregulated in kidneys of the cpk polycystic mouse model (20). We also investigated the expression of the IL13Rα2 receptor, which lacks the intracellular signaling domain and is thought to be decoy receptor and inhibitor of the STAT6 pathway (21). Strikingly, the IL13Rα2 receptor is expressed in control kidneys but is strongly down-regulated in cysts (Fig.…”
Section: Stat6supporting
confidence: 92%
“…This result is consistent with a previous gene-expression study in which the IL4Rα and IL13Rα1 chains were reported to be upregulated in kidneys of the cpk polycystic mouse model (20). We also investigated the expression of the IL13Rα2 receptor, which lacks the intracellular signaling domain and is thought to be decoy receptor and inhibitor of the STAT6 pathway (21). Strikingly, the IL13Rα2 receptor is expressed in control kidneys but is strongly down-regulated in cysts (Fig.…”
Section: Stat6supporting
confidence: 92%
“…IL-13 also binds to the other IL-13 receptor subtype a2 (IL-13Ra2) with an even higher affinity. This receptor has been thought to be a decoy receptor due to its short cytoplasmic tail, but it has been shown that IL-13Ra2 may have some signalling capabilities, regulating IL-13 signalling pathways (Tabata and Khurana Hershey, 2007;Andrews et al, 2009). In the canonical pathway triggered by IL-4 and IL-13, binding of either IL-4 to IL-4Ra in IL-4R Type 1 or 2, or IL-13 to IL-13Ra1 in IL-13 receptors results in an activation of janus tyrosine kinase 1 (JAK1), which leads to phosphorylation of tyrosine residues of IL-4Ra, which subsequently liaisons with the transcription factor signal transducers and activators of transcription 6 (STAT6).…”
Section: Introductionmentioning
confidence: 99%
“…IL-13Ra2 is present on the cell membrane, intracellularly, and in a soluble form. Cell membrane IL-13Ra2 receptors may have some signalling capabilities, but soluble IL-13Ra2 receptors are critical endogenous modulators of IL-13 responses and may, therefore, have a more complicated function than previously thought [29]. IL-13Ra2 is upregulated in cells with heightened responses to IL-13, and increased expression levels of the receptor subunits IL-4Ra and IL-13Ra2 have been reported in fibroblasts from surgical lung biopsies of patients with idiopathic interstitial pneumonia [30,31].…”
mentioning
confidence: 99%